Legal Position of Crown Witnesses as Evidence in Corruption Crime Trials - Fernando, Youngky (The International Journal of Education Management and Sociology, 2022)
The aim of this research is to find out the position of crown witnesses in the criminal justice process for corruption. And the strength of evidence against crown witnesses in corruption cases. The research method uses descriptive qualitative methods with normative law. Data collection techniques include observation to observe the legal status of crown witnesses. In-depth interviews with key informants to obtain accurate and valid data. Documentation study with a number of data from existing archives as well as notes from the trial. The results of the research show that basically the strength of the evidence of crown witnesses is the same as that of witnesses in general and is in accordance with applicable legal provisions. The strength of the evidence of the crown witness regarding the issue of corruption as valid and convincing evidence as the strength of the evidence of the crown witness has met the applicable requirements.